The Impact of Spatial Transformation: The Case Study of Southern Marmara Region - Akdemir, İlhan Oğuz; Türkoğlu, Emrah (Göç İdaresi Başkanlığı, 2022)
Migration; It is the change of geographical environment of man, but changing the place should not be seen as the abandonment of the previous way of life. Migration is not a rupture. When one migrates, language, identity and culture migrate together. In the new environment, the new lifestyle necessarily bears traces of migrating culture and language. In forced displacement (political repression, wars, disasters, etc.), one thinks that he has left everything behind, but the "suitcase of culture" is always with him. The cultural suitcase created "Allokton Balkan settlements" in Anatolia and Thrace. Thousands of people from the Balkans and Caucasus regions left their lands and settled in Anatolia as a result of wars and political repression. South Marmara Section is one of the preferred places for migrants coming to Anatolia. This forced migration plays a decisive role in the redistribution of the population to the place and the shaping of the place. As a result of the mass population movements formed with forced migrations, migration plays a role in transforming not only population, socio-economic, cultural and political structures, but also places. The migrant sites formed in the cities are examples of the impact of migration on the place and its transformation of the place. In this research, the transformation of land, dwellings and cultural structure was discussed in order to easily distinguish migrant settlements from traditional Anatolian village texture in rural areas and neighborhood texture in cities. For this purpose, field research was carried out in the South Marmara section using semi-structured interview techniques in urban and rural areas where migrants live intensively in order to analyze the impact of migration influxes from the Balkans and Caucasus on the transformation of the place. The findings from the field research were evaluated using qualitative and quantitative research methods.

Göç; İnsanın coğrafi ortamını değiştirmesidir, ancak mekânın değişmesi insanın önceki yaşam tarzını bırakması olarak görülmemelidir. Göç bir kopuş değildir. İnsan göç ederken dili, kimliği, kültürü de beraber göç eder. Yeni ortamda, yeni yaşam tarzı, mutlaka göç eden kültür ve dilden izler taşır. Zorla yerinden edilmişliklerde (siyasi baskılar, savaşlar, afetler vs.) insan her şeyini geride bıraktığını düşünür, fakat “kültür bavulu” daima yanındadır. Kültür bavulu, Anadolu ve Trakya’da “Allokton Balkan yerleşim birimleri” meydana getirmiştir. Balkanlar ve Kafkasya bölgelerinden, savaşlar ve siyasi baskılar sonucunda binlerce insan topraklarını terk ederek Anadolu’ya yerleşmişlerdir. Anadolu’ya gelen göçmenler için iskân yeri olarak tercih edilen yerlerin başında Güney Marmara Bölümü gelmektedir. Bu zorunlu göç, nüfusun mekâna yeniden dağılımı ve mekânın şekillenmesinde belirleyici rol oynamaktadır. Zorunlu göçler ile birlikte oluşan kitlesel nüfus hareketleri sonucunda göçün sadece nüfusu, sosyo-ekonomik, kültürel ve siyasi yapıları değil aynı zamanda mekânları da dönüştürmesinde de rol oynamaktadır. Kentlerde oluşan göçmen mahalleri göçün mekân üzerindeki etkisine ve mekânı dönüştürmesine örnek teşkil etmektedir. Bu araştırmada göçmen yerleşmelerinin, kırsal kesimde geleneksel Anadolu köy dokusundan, kentlerde ise mahalle dokusundan kolaylıkla ayırt edilebilmesi, mekânsal olarak arazinin, meskenlerin ve kültürel yapının dönüşümü ele alınmıştır. Bu amaçla Güney Marmara bölümünde, Balkanlar ve Kafkasya’dan gelen göç akınlarının mekânın dönüşümüne etkisini analiz edebilmek için göçmenlerin yoğun olarak yaşadıkları kentsel ve kırsal mekânlarda yarı yapılandırılmış görüşme teknikleri kullanılarak saha araştırması yapılmıştır. Saha araştırmasından elde edilen bulgular ise nitel ve nicel araştırma yöntemleri kullanılarak değerlendirilmiştir.
Göçlerin Mekânın Dönüşümüne Etkisi: Güney Marmara Bölümü Örneği